Correlation between lymphopenia and other hematological parameters with duration of hospital stay as a measure of severity in Covid-19: a retrospective study - Ila Singh; Vaishali D. Kotasthane; Dhananjay S. Kotasthane (The Egyptian Journal of Internal Medicine, 2024)
Abstract Purpose The SARS-CoV-2 (corona) virus is evolving fast because of the scale at which it has infected people around the world. Updated data is needed to manage Covid-19 efficiently with limited resources. After thorough literature review, there were very few studies that correlated variation of hematological parameters with duration of hospital stay. Here, the aim of the study was to determine correlation between variation in hematological parameters and duration of hospital stay as a predictor of severity of disease. Methodology The study was conducted at central laboratory of HIMS, Varanasi. The present study was an observational study done retrospectively. The study duration was from 1st July, 2020 to 30th October, 2020. RT-PCR-positive confirmed cases admitted in the institute whose CBC data was available over a period of multiple days were included in the study to find out the correlation. Study design Patients were categorized into two study groups. Group I (A and B): duration of hospital stay from 2 to 10 days and Group II (A, B, and C): duration of hospital stay more than 11 days. Chi-square test was applied to both the groups to see whether correlation between variation in hematological parameters and duration of hospital stay was significant or not. Result A total of 276 Covid-19 patients were included in the study. Patients were divided into groups and subgroups according to the duration of hospital stay. A total of 50% (103) of patients in Group I (hospital stay from 2 to 10 days) had lymphopenia as compared to 72.86% (51) of patients with lymphopenia in Group II (hospital stay from 11 to 40 days). Similarly, 44.17% (91) of patients in Group I had leukocytosis as compared to 72.86% (51) of patients with leukocytosis in Group II. The percentage increase in lymphopenia and leukocytosis in Group II was same, and this increase was found to be statistically significant (p-value < 0.05). Both these variables were increasing with increase in days of hospital stay. Conclusion Hence, to conclude, complete blood count parameters especially lymphopenia and leukocytosis are most significant and economical in guiding the management protocol of Covid-19 patients as well as in predicting the number of days of hospital stay.